Minding mentalizing - convergent validity of the Mentalization Breakdown Interview - Ulvestad, Dag Anders; Johansen, Merete Selsbakk; Kvarstein, Elfrida Hartveit; Pedersen, Geir; Wilberg, Theresa (Frontiers in Psychiatry, 2024)
Objectives: Mentalizing difficulties are central to borderline personality disorder (BPD), have severe consequences, and are an explicit focus in mentalization-based treatment. The significance of mentalizing capacity as a predictor or mediator of change is however still uncertain due to a scarcity of research. The Mentalization Breakdown Interview (MBI) was developed as a time saving tool for studying psychotherapy processes and outcome in borderline pathology. This study aimed to investigate the convergent validity of reflective functioning (RF) ratings based on the MBI (MBI-RF) by a comparison with the gold standard, i.e., RF assessments based on the Adult Attachment Interview (AAI-RF). A secondary aim was to investigate how MBI-RF relates to core symptoms of BPD, levels of functional impairment and symptom distress compared with AAI-RF. Method: Forty-five patients with BPD or significant BPD traits were included. MBI-RF and AAI-RF were rated using the Reflective Functioning Scale. Levels of MBI-RF and AAI-RF and the correlation between the measures were calculated, as well as their associations with the Difficulties in Emotion Regulation Scale, Levels of Personality Functioning-Brief Form 2.0, Work and Social Adjustment Scale, Patient Health Questionnaire, Depression, Generalized Anxiety Disorder-7, self-harm, suicide attempts, and PD diagnostics. Results: The correlation between MBI-RF and AAI-RF was 0.79 (p<0.01), indicating high convergent validity. There were few significant associations between MBI-RF and AAI-RF and clinical measures. Conclusions: The study provides support for the convergent validity of the MBI as a BPD-focused RF assessment method. The MBI has the potential as a time saving, reliable and valid method to be applied in treatment research on patients with borderline pathology. The results indicate that measures of MBI-RF and AAI-RF are different from clinical symptoms.